The Effect of Index Card Match on Cognitive Learning Outcomes in Multiplication Material in Elementary Schools - Annisa Nur Aulia Arrazaq; Muhammad Abduh (Universitas Negeri Makassar, 2023)
Lack of interest in learning multiplication math causes a lack of interest in learning math and provides unsatisfactory results. Researchers tried to conduct experimental research in applying the Index Card Match learning model to the learning outcomes of multiplication math at SDN 1 Danyang Purwodadi. The approach used is a quantitative approach with a pre-experimental method with a One Group Pretest Postest design. Data collection techniques used are tests, observations, interviews and documentation. While data analysis using normality test and Simple Paired T-Test hypothesis test. The results of this study are hypothesis testing on pretests and postests which get results of 0.000 <0.05 H0 is rejected and Ha is accepted. From these results, it means that the application of the Index Card Match model has an influence on the cognitive learning outcomes of multiplication math of grade IV students of SDN 1 Purwodadi.